Diseño y construcción de un abrepuertas automático casero para usuarios de sillas de ruedas - Macías, Héctor; Alvarez, Michel; Letechipia, Jorge (Revista Mexicana de Ingenieria Biomedica, 2003)
Wheelchair users usually have difficulties opening and closing doors. Automatic door openers give independence to wheelchair users by allowing them to go in and out of their homes in an autonomous way. To increase the safety and independence of wheelchair users we designed an automatic door opener. The design took into consideration the characteristics of commercial door openers, the needs of potential users and the international standard for these devices. This work describes the design and construction of an automatic door opener for home use that is well adapted to Mexican wheelchair users. It also presents the advantages of our device over commercial door openers as well as some suggested modifications to improve the design.